Changing Trends in Eye-Related Complaints Presenting to the Emergency Department in Beirut, Lebanon, over 15 Years - Haytham I. Salti; Carl-Joe Mehanna; Bachir Abiad; Nicola Ghazi; Samih Raad; Anita Barikian; Randa Haddad; Adnan Ashkar; Elie Harmouche; Elie Zaghrini; Afif Mufarrij (Journal of Ophthalmology)
Objective. To report the 15-year trend in ophthalmic presentations to the emergency department (ED) at the only medical center in Lebanon that provides 24-hour ophthalmologic care. Methods. Retrospective review of 1967 patients presenting to the ED with eye-related complaints between September 1997 and August 1998 and between September 2012 and August 2013. Diagnoses were classified into 4 categories according to the International Society of Ocular Trauma and include penetrating eye injuries, nonpenetrating eye trauma, nontraumatic ophthalmic emergencies, and nontraumatic, nonurgent ophthalmic conditions. Results. One thousand sixty eye-related presentations out of 39,158 total ED visits (2.71%) presented in 1997 compared to 907 out of 46,363 in 2012 (1.96%). Penetrating and nonpenetrating eye emergencies decreased between 1997 and 2012 (7.17% to 4.19%, p=0.003 and 52.64% to 29.00%, p<0.001, resp.) while nonurgent cases increased from 30.19% to 53.47% (p<0.001). 57% of patients were covered by third-party guarantors in 1997 versus 73% in 2012. Conclusion. Our results demonstrate a significant increase in nonurgent cases in parallel with the proportion of third-party payers, an issue to be addressed by public health policies and proper resource allocation. A detailed nationwide review is needed to make solid recommendations for the management of ophthalmologic presentations in the ED.